Happy and healthy: The hypothesis of correlation between subjective well-being and psychological health and its role in late adulthood - HORBAL, IRYNA (Journal of Education Culture and Society, 2020)
Subjective well-being as an emotional-cognitive assessment of person’s life is an impor-tant aspect of psychological health and positive functioning in general. The hypothesis of connection between subjective well-being, psychological well-being and psychological health is presented. This correlation is very important in late adulthood for ensuring happy obsolescence but has some specifi c peculiarities due to the elderly people’s age and indivi-dual traits. Subjective well-being is a background for effective inner work of summarizing person’s previous life that is the main purpose in old age